Lipid metabolism regulation by dietary polysaccharides with different structural properties - Yin, Dafang; Zhong, Yadong; Liu, Huan; Hu, Jielun (International journal of biological macromolecules, 2024)
Lipid metabolism plays an important role in energy homeostasis maintenance in response to stress. Nowadays, hyperlipidemia-related chronic diseases such as obesity, diabetes, atherosclerosis, and fatty liver pose significant health challenges. Dietary polysaccharides (DPs) have gained attention for their effective lipid-lowering properties. This review examines the multifaceted mechanisms that DPs employ to lower lipid levels in subjects with hyperlipidemia. DPs could directly inhibit lipid intake and absorption, promote lipid excretion, and regulate key enzymes involved in lipid metabolism pathways, including triglyceride and cholesterol anabolism and catabolism, fatty acid oxidation, and bile acid synthesis. Additionally, DPs indirectly improve lipid homeostasis by modulating gut microbiota composition and alleviating oxidative stress. Moreover, the lipid-lowering mechanisms of particular structural DPs (including β-glucan, pectin, glucomannan, inulin, arabinoxylan, and fucoidan) are summarized. The relationship between the structure and lipid-lowering activity of DPs is also discussed based on current researches. Finally, potential breakthroughs and future directions in the development of DPs in lipid-lowering activity are discussed. The paper could provide a reference for further exploring the mechanism of DPs for lipid regulations and utilizing DPs as lipid-lowering dietary ingredients.